Measuring Human-Animal Attachment in a Large U.S. Survey: Two Brief Measures for Children and Their Primary Caregivers - Bures, Regina M.; Mueller, Megan Kiely; Gee, Nancy R. (Frontiers in Public Health, 2019)
Researchers in the human-animal interaction (HAI) field face a challenge in generalizing the impact of pet ownership and companion animal interaction from small samples to larger populations. While researchers in Europe and Australia have included measures of pet ownership and attachment in surveys for some time (e.g., the Avon Longitudinal Study of Parents and Children), survey researchers in the United States have been slow to incorporate questions related to HAI in population representative studies. One reason for this may be that many of the current HAI-related measures involve long, complex scales. From the survey administration perspective, using complex scales is costly in terms of both time and money. The development and validation of brief measures of HAI will facilitate the inclusion of these measures in larger surveys. This paper describes the psychometric properties of two brief attachment measures used in the first population-representative study of child development in the United States that includes HAI items, the 2014 Panel Study of Income Dynamics (PSID) Child Development Supplement (CDS). We use two measures derived from the 29 item CENSHARE Pet Attachment Survey, one for children aged 8–17 (6-items) and one for the primary caregiver (3 items). The results suggest that such brief measures of attachment to pets are psychometrically valid and are a practical method of measuring HAI attachment in larger surveys using only a few survey items. We encourage HAI researchers to work with other ongoing surveys to incorporate these and comparable HAI measures.